The Development Of Waqf For Poverty Alleviation In Adamawa State, Nigeria - Yakubu, Aminu (2023)
Waqf is an Islamic endowment with the primary goal of assisting and alleviating poverty in Muslim nation. By given its numerous advantages, waqf has undeniably the ability to improve a society`s standard of living. Waqf practice addresses poverty, unemployment, and lack of support by providing human relief, financial assistance, and social necessities. However, the fact that Adamawa state is still plagued by the societal menace of poverty is humorous. Relatively disturbing is the frequency of the social threat of poverty is increasing in the state that is affecting educational, health and social life of people. Unemployment among youth and adults is rising rapidly across the state, contributing to the state`s terrible poverty. Many children are exploited, and some of them are forced to work in unhealthy and dangerous situations as a result of their parent’s failure to pay for their needs and sustenance. The purpose of this research is to look into waqf practice in Adamawa state, Nigeria, as well as the administration, institutions, and their effects on poverty alleviation in Adamawa state. In addition, the study discusses how waqf practice can be used to enhance economy and to create job opportunity. The study also discusses suitable recommendations and resolutions to the social and economic challenges confronting the state. This study used basic qualitative research method to examine the waqf practice activities in Adamawa state. Interview were completed with twelve informants from the different categories of people within Adamawa state, which include Islamic scholars, academicians, and waqf practitioners.